Barron's E-Z English - Diamond, Harriet (Barron's Educational Series, 2009)
From the Publisher: The authors demonstrate the process of translating coherent thinking into coherent grammar, with attention to all parts of speech, verb tenses and moods. Examples of proper sentence construction deal with simple, compound, and complex sentences, and demonstrate agreement in number, correct sequence of tenses, and more. Other topics covered include punctuation, vocabulary building, and writing style. Exercises with answers appear throughout the text. Barron's continues its ongoing project of updating, improving, and giving handsome new designs to its popular list of Easy Way titles, now re-named Barron's E-Z Series. The new cover designs reflect the books' brand-new page layouts, which feature extensive two-color treatment, a fresh, modern typeface, and more graphic material than ever. Charts, graphs, diagrams, instructive line illustrations, and where appropriate, amusing cartoons help to make learning E-Z. Barron's E-Z books are self-teaching manuals focused to improve students' grades across a wide array of academic and practical subjects. For most subjects, the skill level ranges between senior high school and college-101 standards. In addition to their self-teaching value, these books are also widely used as textbooks or textbook supplements in classroom settings. E-Z books review their subjects in detail, using both short quizzes and longer tests to help students gauge their learning progress. All exercises and tests come with answers. Subject heads and key phrases are set in a second color as an easy reference aid.